2019
DOI: 10.1002/jrs.5621
|View full text |Cite
|
Sign up to set email alerts
|

Universal detection of body fluid traces in situ with Raman hyperspectroscopy for forensic purposes: Evaluation of a new detection algorithm (HAMAND) using semen samples

Abstract: Towards closing the technological gaps in forensic science, Raman spectroscopy has been a boon to the field. One area that this technique shows exceptional promise is in body fluid identification and characterization, but substrate interference remains a major impediment to its practical implementation. Here, we present an approach for the universal detection of body fluids regardless of the substrate. This approach, which is based on Raman hyperspectroscopy and multivariate curve resolution, was applied to da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 43 publications
(60 reference statements)
0
11
0
Order By: Relevance
“…Sample solutions were prepared and sealed in containers prior to Raman measurements. HAMAND (hypothetical addition multivariate analysis with numerical differentiation) is a numerical version of the well-known standard addition method. , It combines the principle of the standard addition method with multivariate curve resolution, hence separating out the known target spectrum from a complicated system spectrum. A number of hypothetical model spectra S j are generated numerically by adding to the observed the known pure water spectrum S std multiplied with hypothetical addition coefficients c j : S j = S unkn + c j × S std , here S unkn means the solution spectra.…”
Section: Methodsmentioning
confidence: 99%
“…Sample solutions were prepared and sealed in containers prior to Raman measurements. HAMAND (hypothetical addition multivariate analysis with numerical differentiation) is a numerical version of the well-known standard addition method. , It combines the principle of the standard addition method with multivariate curve resolution, hence separating out the known target spectrum from a complicated system spectrum. A number of hypothetical model spectra S j are generated numerically by adding to the observed the known pure water spectrum S std multiplied with hypothetical addition coefficients c j : S j = S unkn + c j × S std , here S unkn means the solution spectra.…”
Section: Methodsmentioning
confidence: 99%
“…In other cases, the variation between spectra can be subtle shifts in band position and/or intensity, requiring statistical methods, such as multivariate statistical analysis, to differentiate them. The potential of RS coupled with multivariate statistical analysis was previously demonstrated in many fields including forensics, art, and medicine. Our group has demonstrated the potential of RS coupled with multivariate statistics for the detection of fungal, viral, and bacterial diseases on a broad spectrum of plants. Specifically, we showed that RS could be used for the detection of Candidatus Liberibacter asiaticus that causes Huanglongbing, or citrus greening, on orange and grapefruit trees. , While Raman is quite powerful in detecting distinct chemical groups on a sample surface, its ability to probe deeper layers is limited.…”
Section: Introductionmentioning
confidence: 94%
“…A similar problem has been tackled while Raman spectroscopy was used for the identification of biological stains on various interfering substrates 34 , 35 . Most recently, a multivariate statistical approach has been developed for detecting trace amounts of semen on strongly interfering substrates using Raman spectroscopy 36 .…”
Section: Resultsmentioning
confidence: 99%